Through-culm wall mechanical behaviour of bamboo. (20th August 2019) - Akinbade, Yusuf; Harries, Kent A.; Flower, Chelsea V.; Nettleship, Ian; Papadopoulos, Christopher; Platt, Shawn
Highlights: Study investigates transverse material property gradient through bamboo culm wall. Transverse behaviour does not behave as a fibre-reinforced composite material. Variation if morphology through culm wall identified using microscopy. Culm wall morphology coupled with material property assessment. Abstract: Performance of full-culm bamboo structures is dominated by longitudinal splitting behaviour, often exacerbated by connection details. This behaviour is a function of the transverse properties of this highly orthotropic material. Considerable study of the longitudinal properties of bamboo is available in which it is often concluded that bamboo may be considered as a fibre-reinforced composite material and material properties may be assessed using rule-of-mixture methods. Nonetheless, few studies have addressed the transverse properties of the bamboo culm wall, despite these largely governing full-culm behaviour. This study investigated the transverse material property gradient through the culm wall and attempts to connect the mechanical results to physical observations and phenomena. Most importantly, the study demonstrates that the complex transverse behaviour of bamboo does not appear to behave as a classic fibre-reinforced composite material in the direction transverse to the fibres. In this study, five different bamboo species, Phyllostachys edulis, Phyllostachys bambusoides, Phyllostachys meyeri, Phyllostachys nigra, and Bambusa stenostachya were tested using a modification of the flat-ring flexure test to obtain a measure of the transverse tensile capacity of the bamboo. Microscopy analyses are used to qualitatively describe the culm wall architecture and to quantitatively assess the failure modes through the culm wall thickness.